Pengukuran Indeks Bias Larutan untuk Mengetahui Kadar Gula dalam Tebu dengan Menggunakan Metode Difraksi Fraunhofer Celah Tunggal - Lalu A. Didik; Irfan Safarwadi; Muslimah Muslimah (Universitas Islam Negeri (UIN) Mataram, 2021)
Refractive index measurements of sugar solutions have been carried out in several concentrations. The method used is fraunhofer diffraction. The equation of relationship between the concentration of the sugar solution and the refractive index based on the results of the linear fitting can be written as, Where n is the refractive index of the sugar solution and x is the solution concentration. From this equation, a fairly small gradient value of 1.59145 is obtained. This shows that a 1% increase in the concentration of the sugar solution will cause the refractive index to decrease by 1.59145. The refractive index of the solution changes when the concentration changes. The refractive index of the solution increases with increasing concentration of the solution. This is because along with the increase in concentration, more glucose is found in the sugar solution. As a result, the solution will be more concentrated because the glucose molecules that are arranged are getting denser. The above equation is used to calculate the concentration of sugar in sugar cane. It was found that brown sugar cane had a concentration of 33.38% compared to 26.34% in yellow sugarcane. While the measurement of the concentration of sugar cane in different planting areas shows almost the same results, this is because the level of accuracy of the tool is still large when compared to the difference in the concentration of the sugar solution.